2004
DOI: 10.1152/japplphysiol.00840.2003
|View full text |Cite
|
Sign up to set email alerts
|

Decreased exhaled nitric oxide as a marker of postinsult immune paralysis

Abstract: Nitric oxide (NO) regulates neutrophil migration and alveolar macrophage functions such as cytokine synthesis and bacterial killing, both of which are impaired in immune paralysis associated with critical illness. The aim of this study was to determine whether NO is involved in immune paralysis and whether exhaled NO measurement could help to monitor pulmonary defenses. NO production (protein expression, enzyme activity, end products, and exhaled NO measurements) was assessed in rats after cecal ligation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…The defect in NO synthesis may favor both vasoocclusive and infectious events. The decrease in exhaled NO in SAD mice could be an indirect measure of innate immunity impairment occurring after peritonitis, as previously suggested (15), justifying the enhanced mortality rate compared with control mice. Accordingly, Holtzclaw and colleagues (14) showed that intraperitoneal endotoxin challenge was associated with significant increase in mortality in transgenic sickle mice compared with control animals.…”
Section: Morris and Colleaguessupporting
confidence: 63%
See 3 more Smart Citations
“…The defect in NO synthesis may favor both vasoocclusive and infectious events. The decrease in exhaled NO in SAD mice could be an indirect measure of innate immunity impairment occurring after peritonitis, as previously suggested (15), justifying the enhanced mortality rate compared with control mice. Accordingly, Holtzclaw and colleagues (14) showed that intraperitoneal endotoxin challenge was associated with significant increase in mortality in transgenic sickle mice compared with control animals.…”
Section: Morris and Colleaguessupporting
confidence: 63%
“…Immunoblotting for iNOS and endothelial NOS (eNOS) proteins was performed as described elsewhere (15). Briefly, the primary antibody against eNOS 3 protein (eNOS or NOS 3, Transduction Laboratory, Lexington, KY) or iNOS 2 protein (iNOS or NOS 2, Transduction Laboratories.…”
Section: Western Blotting Of Inducible Nos 2 and Endothelial Nos 3 Prmentioning
confidence: 99%
See 2 more Smart Citations
“…NO is a broad-spectrum messenger involved in all biological processes including immunity (4) and also has direct antimicrobial activity (5). Some arguments suggest its usefulness for predicting immunosuppression and consequently the risk of nosocomial infection: (a) its fraction has been shown to be decreased in upper and lower respiratory tracts of patients with cystic fibrosis, and its deficiency has experimentally been shown to favor Pseudomonas aeruginosa infection (6,7); (b) a beneficial effect of NO inhalation on bacterial clearance of P. aeruginosa has been shown in animals (8); (c) immunonutrition using nutriments with L-arginine, the precursor of NO synthesis, has been associated with a reduction of nosocomial infections in surgical patients (3); and (d) we demonstrated that a decrease in exhaled NO constitutes a marker of postaggressive immunosuppression in an experimental model of sepsis (9). Besides this biological plausibility, NO measurement in the respiratory tract can be easily and immediately obtained at the bedside and is already used to assess various respiratory diseases (10).…”
Section: Introductionmentioning
confidence: 72%